2014
DOI: 10.1530/rep-13-0010
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of uterine fluid during the pre-implantation period of pregnancy in cattle

Abstract: The aims of this study were i) to characterize the global changes in the composition of the uterine luminal fluid (ULF) from pregnant heifers during pregnancy recognition (day 16) using nano-LC MS/MS; ii) to describe quantitative changes in selected proteins in the ULF from days 10, 13, 16 and 19 by Isobaric tags for Relative and Absolute Quantification (iTRAQ) analysis; and iii) to determine whether these proteins are of endometrial or conceptus origin, by examining the expression profiles of the associated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 62 publications
(64 reference statements)
8
94
0
1
Order By: Relevance
“…By contrast, in another study with the use of bovine OF before fertilization in vitro, it was found that expression of AKR1B1 was affected by the quality of the blastocysts (CebrianSerrano et al 2013). The protein encoded by AKR1B1 has also been found in the uterine luminal fluid of pregnant heifers on Day 16 (Forde et al 2014). In addition, high glucose concentrations in culture media could lead to upregulation of aldose reductase and subsequent accumulation of sorbitol in cytoplasm and activation apoptotic pathways (Wirtu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in another study with the use of bovine OF before fertilization in vitro, it was found that expression of AKR1B1 was affected by the quality of the blastocysts (CebrianSerrano et al 2013). The protein encoded by AKR1B1 has also been found in the uterine luminal fluid of pregnant heifers on Day 16 (Forde et al 2014). In addition, high glucose concentrations in culture media could lead to upregulation of aldose reductase and subsequent accumulation of sorbitol in cytoplasm and activation apoptotic pathways (Wirtu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, we were able to demonstrate that BSA, purine nucleoside phosphorylase (PNP), and heat shock 70 kDa protein 5 (HSPA5) showed a type 1, type 3, and type 3 validation profile respectively (Muñ oz et al 2012). The cow endometrium predominantly transcribes PNP (Forde et al 2014). Unaltered PNP and HSP70 levels indicated no changes in purine metabolism and no stress resulting from cytotoxic damage.…”
Section: Response Models In the Uterine Fluid And Endometriummentioning
confidence: 99%
“…The histotroph consists of different substances (e.g. amino acids, carbohydrates, proteins, lipids) transported into the uterine lumen by endometrial epithelial cells from the blood and as specific secretory products encoded by genes expressed in the endometrial epithelium (Bazer, 1975;Gray et al, 2001;Forde et al, 2014). Embryo development in uterine-gland knock-out sheep has shown to be retarded from day 9-14, indicating the importance of the endometrial epithelial secretions (Gray et al, 2002).…”
Section: Preparations In the Embryo Recipientmentioning
confidence: 99%